Novell - Dulaney, Emmett (Sams, 2004)
This official Novell Press Study Guide is your key to reviewing the fundamentals of installing, running, and administering SUSE LINUX so that you can pass Novell Practicum: 050-069, Novell's Certified Linux Professional exam, and become a Novell CLP. Expert trainer and curriculum developer Emmett Dulaney brings you the practical knowledge, tested techniques, real-world scenarios, and hands-on lab exercises you need to help you get the CLP certification from Novell.